2004
DOI: 10.1017/s0954579404044542
|View full text |Cite
|
Sign up to set email alerts
|

The expression and regulation of negative emotions: Risk factors for young children's peer victimization

Abstract: Using a short-term longitudinal design, internalizing and externalizing emotions were examined as risk factors for being victimized by peers in early childhood. Regulation, aggression, and withdrawal were also tested as mediators. We found that anger, mediated by aggression and regulation, positively predicted being victimized, although the way in which anger related to victimization risk varied for boys and girls and across time. These findings were robust, particularly for girls, attesting to the importance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
116
1
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 166 publications
(126 citation statements)
references
References 42 publications
8
116
1
1
Order By: Relevance
“…On the other hand, however, aggressive children are sometimes isolated from the mainstream peer group. In the extreme, mainstream peers may respond to aggressive children with disapproval in the form of victimization or exclusion (Hanish et al, 2004), leaving few options for interaction partners other than aggressive peers.…”
Section: Homophilymentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, however, aggressive children are sometimes isolated from the mainstream peer group. In the extreme, mainstream peers may respond to aggressive children with disapproval in the form of victimization or exclusion (Hanish et al, 2004), leaving few options for interaction partners other than aggressive peers.…”
Section: Homophilymentioning
confidence: 99%
“…On the other hand, however, aggressive children are sometimes isolated from the mainstream peer group. In the extreme, mainstream peers may respond to aggressive children with disapproval in the form of victimization or exclusion (Hanish et al, 2004), leaving few options for interaction partners other than aggressive peers.Although homophily is a well-established phenomenon, it is not clear what specific behavioral factors predict externalizing homophily among young children, though the presence of externalizing behaviors and the absence of socially competent behaviors are likely candidates. We investigated several externalizing and socially competent predictors of homophily, considering the relative importance of each in determining exposure to externalizing peers.…”
mentioning
confidence: 99%
“…Miller, Gouley, Seifer, Dickstein & Shields found that children with dysregulation show more levels of anger and aggresion. Also Calkins, Gill, Johnson, and Smith ( 1999);Cole, Zahn-Waxler, Fox, Usher, and Welsh (1996), Hanish et al, ( 2004) found that children with poor emotion regulation exhibit aggressive and under controlled behaviors in social interactions, experience isolation and rejection in peer contexts, no conflicts declared.…”
Section: Discussionmentioning
confidence: 99%
“…Araştırmalar çocukların sosyal yetkinlik konusunda sıkıntı yaşamalarındaki etkili faktörler arasında onların saldırganlık, kızgınlık, içedönüklük ve anksiyete durumları olduğuna işaret etmektedir (Hanish, Eisenberg, Fabes, Spinrad, Ryan ve Schmidt, 2004;Reeve, Jang, Carrell, Jeon ve Barch, 2004).…”
Section: Introductionunclassified